Willie MacKenzie and Katie Martin interviewed by John Callaghan in Callaghan collection. - MacKenzie, Willie; Martin, Katie, 1909-; Callaghan, John (1961)
Folkloric recording.
Aboriginal and Torres Strait Islander people are advised that this recording may contain names and voices of deceased persons.
Recorded on 21 November 1961.
Digital master available
Timed summary available.
Keywords: MacKenzie, Willie -- Interviews; Martin, Katie, -- 1909- -- Interviews; Songs, Aboriginal Australian -- Queensland; Music - Vocal; Dungidjau people (E20) (Qld SG56-14); Duungidjawu language E20.; Dalla people (E25) (Qld SG56-10); Dalla language E25.; Kilcoy (SE Qld SG56-10)